Evaluasi Kinerja Keuangan BUMN Sektor Ketenagalistrikan: Studi Kasus PT PLN (Persero) UP3 Pekanbaru - Aulya Putri Andini Nasution; Kartini Kartini (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to evaluate the financial performance of PT PLN (Persero) UP3 Pekanbaru for the period 2023–2024 using profitability, liquidity, activity, and solvency ratios, based on the national assessment standard KEP-100/MBU/2002 for state-owned enterprises. The analysis seeks to determine the company’s financial effectiveness and its implications for operational sustainability. This research employed a quantitative descriptive approach using secondary financial data. Financial ratios including Return on Equity, Return on Asset, Current Ratio, Cash Ratio, Receivable Turnover, Inventory Turnover, Total Asset Turnover, and equity-to-total asset ratio were calculated and assessed against the BUMN performance criteria established by the Ministry of State-Owned Enterprises. The results indicate an increase in ROE from 12% to 13% and ROA from 8% to 9%. However, this improvement was driven by a decrease in equity and assets rather than an increase in net income. Liquidity ratios remained below ideal standards, activity ratios were relatively stable, and solvency ratios were categorized as highly healthy. The overall performance score improved from 29.5 to 30.5, reflecting moderate progress. This study provides empirical evidence on the financial sustainability of a national electricity utility and highlights the importance of asset optimization and liquidity enhancement. The findings serve as a strategic reference for policymakers and offer a foundation for future research in public sector financial performance.suggest that companies need to be more proactive in fulfilling social and environmental responsibilities to enhance investor trust and market value.